2021
DOI: 10.1093/bjs/znab194
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of nodal involvement in rectal cancer after chemoradiotherapy

Abstract: Background The purpose of this study was to investigate the prevalence of ypN+ status according to ypT category in patients with locally advanced rectal cancer treated with chemoradiotherapy and total mesorectal excision, and to assess the impact of ypN+ on disease recurrence and survival by pooled analysis of individual-patient data. Methods Individual-patient data from 10 studies of chemoradiotherapy for rectal cancer were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The 5-year overall survival rate of patients with non-pCR in our study was 75.2%, and a study using National Cancer Database (NCDB) data showed a survival rate of 73% (35), which was similar to our findings. Meanwhile, a meta-analysis found that patients with ypN0 and ypN+ disease had 5-year overall survival rates of 83.2% and 63.4%, respectively (34). The rate was also comparable to our study, which was 78.9% and 66.3%, respectively.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The 5-year overall survival rate of patients with non-pCR in our study was 75.2%, and a study using National Cancer Database (NCDB) data showed a survival rate of 73% (35), which was similar to our findings. Meanwhile, a meta-analysis found that patients with ypN0 and ypN+ disease had 5-year overall survival rates of 83.2% and 63.4%, respectively (34). The rate was also comparable to our study, which was 78.9% and 66.3%, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…This was consistent with our usual clinical perception. According to a meta-analysis, higher T stage was associated with a higher rate of lymph node metastasis (34). Wang et al found that the risk of lymph node metastasis following neoadjuvant chemoradiotherapy was related to T stage, with the deeper the invasion, the greater the risk of lymph node metastasis (32).…”
Section: Discussionmentioning
confidence: 99%
“…TRG alone is not definitive. The ypT and ypN category remain the most important prognostic factors [ 28 ]. We also noted that the levels of HEP2 and GELS correlated with ypT, GELS correlated with ypN, while the level of S10A8 correlated with distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a cCR after (chemo)radiotherapy, the prevalence of involved lymph nodes is low, approximately 7%. 38 Considering this low prevalence and the risk of overstaging by MRI, the expert panel felt that the presence of 1 single suspicious mesorectal lymph node should not be the decisive factor for organ preservation because it may well be a false-positive finding. Lymph nodes can relatively easily be monitored on MRI, and further observation with careful monitoring of the suspected residual lymph node might be justified, especially when there is a cCR or subcategory "high" nCR in the rectal lumen.…”
Section: Weeks After Chemoradiotherapymentioning
confidence: 99%